Artificial Intelligence and Communication Between Higher Education Institutions and International Students - Knez, Jana; Podbregar, Iztok; Akrap, Gordan (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
This article presents the factors of communication in HEIs and specifically introduces them in relation to artificial intelligence (AI) and HEIs' communication with international students. Key communication factors such as clarity, transparency, timeliness, responsiveness and personalisation are presented. In relation to the communication factors, we find that AI allows for more efficient information delivery, rapid responsiveness and tailoring of communication to the specific needs of students. In addition to these benefits, AI contributes to improving the transparency and proactivity of communication, which enhances students' trust and long-term commitment to the institutions. Nevertheless, limitations remain in dealing with complex and emotionally sensitive issues, highlighting the need for a combination of AI systems and human support.